Assessing Semantic Development Through an Object Description Task - Olson, Dorothy M. (University of Wisconsin-Stevens Point, 1975)
For the purpose of assessing semantic development in kindergarten-age children, an object description task utilizing specific probe questions was constructed. Test administration procedures included both a spontaneous format and a probe format for each child. Subjects consisted of 28 children between the ages of 5-4 and 6-5, with a mean age of 5-10. Responses were recorded utilizing a fifteen unit categorical system. Data analyses revealed the presence of statistically significant differences among the frequencies with which responses were given for each of the fifteen categories. Differences in the number of responses given for each of the six test objects were also significantly different. A comparison of descriptions given for a novel object with those given for familiar objects also yielded statistically significant differences. Interpretations of these findings and their clinical implications are discussed.